The Implementation of Cash Waqf Management as National Economic Recovery (PEN) Post-Covid-19 Pandemic - Nahdah Shifani; Rahandy Rizki Prananda (Universitas Islam Sultan Agung, 2023)
The Covid-19 pandemic has had a very bad impact on the Indonesian economy which has fallen sharply due to this pandemic. The author uses a normative juridical research type and uses a qualitative descriptive analysis approach. The government has formulated the National Economic Recovery (PEN) program to protect the national economy. In this context, it is hoped that Islamic social finance can support the National Economic Recovery plan. Money Waqf or Cash Waqf can be used to deal with economic problems that arise. Thus the results of this study are to find out the Management and Development of Waqf Assets in the Form of Cash Waqf, as well as the Implementation of Management of the Cash Waqf Program as National Economic Recovery (PEN) Post the Covid-19 Pandemic.